Detection of multiple human enteropathogens in Norway rats (Rattus norvegicus) from an under-resourced neighborhood of Vancouver, British Columbia. - Lisa K F Lee; Chelsea G Himsworth; Kaylee A Byers; Harveen K Atwal; Gus Gabaldon; Gordon Ritchie; Christopher F Lowe; Nancy Matic; Samuel Chorlton; Linda Hoang; Bruce K Wobeser; Victor Leung (Public Library of Science (PLoS), 2023)
Urban Norway rats (Rattus norvegicus) can carry various human pathogens, and may be involved in pathogen propagation and transmission to humans. From January 31-August 14, 2021, a community outbreak of Shigella flexneri serotype 2a occurred among unhoused or poorly housed people in the Downtown Eastside neighborhood of Vancouver, British Columbia, Canada. The source could not be identified; however, patients reported contact with rats, and previous studies indicated transmission of rat-associated zoonotic pathogens among the unhoused or poorly housed residents of this neighborhood. The study objective was to determine if rats trapped in the outbreak area were carriers of Shigella spp. and other zoonotic enteric pathogens. From March 23-April 9, 2021, 22 rats were lethally trapped within the outbreak area. Colonic content was analyzed using the BioFire FilmArray Gastrointestinal (multiplex PCR) panel for human enteropathogens, which detected: Campylobacter spp. (9/22), Clostridioides difficile (3/22), Yersinia enterocolitica (5/22), Cryptosporidium spp. (8/22), Giardia duodenalis (5/22), Rotavirus A (1/22), enteroaggressive Escherichia coli (2/22), enteropathogenic E. coli (10/22), and Shigella spp. or enteroinvasive E. coli (EIEC) (3/22). An ipaH PCR assay was used for targeted detection of Shigella spp./EIEC, with five rats positive. Two samples contained insertion sites unique to S. flexneri isolated from the human outbreak. This study highlights the potential for rats to carry a broad range of human pathogens, and their possible role in pathogen maintenance and/or transmission.